The research landscape of ferroptosis in the brain: A bibliometric analysis - Miao, Mengrong; Han, Yaqian; Wang, Yangyang; Yang, Yitian; Zhu, Ruilou; Sun, Mingyang; Zhang, Jiaqiang (Frontiers in Pharmacology, 2022)
Background: Ferroptosis is a newly proposed programmed cell death and has been widely studied in many diseases during the past ten years. However, bibliometric study concentrating on publication outputs and research trends of ferroptosis related to brain is still lacking. Methods: We retrieved publication data in field of ferroptosis in brain from Web of Science Core Collection (WOSCC) on 31 December 2021. Bibliometric analysis was performed by VOSviewer and CiteSpace software. Results: Six hundred and fifty-six documents focus on ferroptosis in brain were published from 2012 to 2021. The number of publications in this field had a steady increase in quantity during past years. Most of publications were from China (338) and the United States (166), while the most productive organizations were the University of Melbourne (34) and University of Pittsburgh (23). Ashley I. Bush was the most productive author, while Scott J Dixon was the most co-cited author. Free radical biology and medicine published the most articles in this field, while Cell was the most cited journal. Among 656 publications, top10 cited documents were cited at least 300 times. Among top20 references with the strongest citation bursts, half of papers had a burst until 2021. Keywords analysis suggested that top20 keywords appeared at least 40 times. “Amyloid precursor protein” was the keyword with strongest bursts. Conclusion: The research on ferroptosis in brain will continue to be highly regarded. The current study analyzed the research landscape of ferroptosis in brain and offered a reference for researchers of this field.